PENGUKURAN KINERJA DENGAN MENGGUNAKAN METODE â€BALANCED SCORECARDâ€ (Studi pada KANINDO Syariâ€™ah Jatim) - Mahtumah, Siti; Fitriyah, Fitriyah (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
The purpose of this study is to measure the performance of Shari’ah KANINDO Malang in East Java by using the Balanced Scorecard (BSC). BSCis a performance measurement method which not only reflects the financial performance, but also non-financial performance (aspects of the customer, internal business processes and learning and growth). The method of analysis in this research is by using descriptive analysis. The research result, the average value for each of the perspective that is the financial perspective is needed to be improved because there are several ratios that are still not as stable as the LDR. Customer perspective, which is indicated by the level of customer satisfaction (customer satisfaction) foward the services provided by KANINDO to the members and the prospective members. In the internal business perspective, it needed targetsin the performance assessment by which it can easily know the barometer of success of a program of work in order the company’s goals can be achieved optimally and the learning and the growth are quite good as indicated by the increased of productivity of employees from year to year. So it can be concluded that the performance of Shari’ah KANINDO Malang of East Java is included in criteria of quite well and it is suggested that KANINDO implements the Balanced Scorecard method for performance appraisal.